2018
DOI: 10.7150/ijbs.21547
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Types 16 and 18 Early-expressed Proteins Differentially Modulate the Cellular Redox State and DNA Damage

Abstract: Oxidative stress has been proposed as a risk factor for cervical cancer development. However, few studies have evaluated the redox state associated with human papillomavirus (HPV) infection. The aim of this work was to determine the role of the early expressed viral proteins E1, E2, E6 and E7 from HPV types 16 and 18 in the modulation of the redox state in an integral form. Therefore, generation of reactive oxygen species (ROS), concentration of reduced glutathione (GSH), levels and activity of the antioxidant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 40 publications
0
55
0
Order By: Relevance
“…In contrast, Cruz-Gregorio and co-workers demonstrated that expression of HR-HPVs E6/E7 does not alter ROS production or catalase activation in C33A cells. (35) Taken together, the observations described above reveal the existence of variable effects of the HPV oncogenes on the expression and/or activity of catalase in different cell systems. Further studies are needed to understand the impact of oncogenes from different HPV types on this important cellular protein and to determine the role of catalase in HPV-mediated pathologies.…”
Section: Induction Of Epithelial Mesenchymal Transition (Emt)mentioning
confidence: 73%
See 1 more Smart Citation
“…In contrast, Cruz-Gregorio and co-workers demonstrated that expression of HR-HPVs E6/E7 does not alter ROS production or catalase activation in C33A cells. (35) Taken together, the observations described above reveal the existence of variable effects of the HPV oncogenes on the expression and/or activity of catalase in different cell systems. Further studies are needed to understand the impact of oncogenes from different HPV types on this important cellular protein and to determine the role of catalase in HPV-mediated pathologies.…”
Section: Induction Of Epithelial Mesenchymal Transition (Emt)mentioning
confidence: 73%
“…4, HaCaT cells containing HPV-18 E5/E6/E7 viral oncogenes exhibited significantly higher levels of oxidised CM-H2DCF probe (CM-DCF) compared to that observed in HaCaT control cells, HaCaT E5 cells, and HaCaT E6/E7 cells, indicating an increase in intracellular ROS. As it has been previously observed that the E6 oncoprotein of HPV-18 enhances ROS production and decreases catalase activity, (35) we questioned if this increment in intracellular ROS in HaCaT cells cotransduced with the three oncogenes could be due to a reduction in the function of the cell antioxidant systems. To assess this, we analysed GSH and catalase levels and their enzymatic activity, and we determined the protein levels of peroxiredoxin 1 (PRX1).…”
Section: Effect Of Hpv-18 E5/e6/e7 Oncogenes In Ros Production and Imentioning
confidence: 99%
“…Cells have a battery of antioxidants, such as glutathione (GSH), superoxide dismutase (SOD) 1, 2 and 3, catalase (CAT), peroxidases (Prxs), and thioredoxins (Trxs), among others, which respond quickly and efficiently against OS [ 98 ]. It has been shown that the co-expression of E2 and E1 from HPV18 decreases GSH levels and SOD1 and 2 activity inducing an increase in ROS levels and DNA damage [ 99 ].…”
Section: Hpv Oncoproteins and Cellular Metabolismmentioning
confidence: 99%
“…Temozolomide (TMZ)-resistant glioma cells showed low levels of ROS and high GSH and glutathione reductase levels, exhibiting greater antioxidant capacity than sensitive cells, suggesting that this redox system may be an important therapeutic target 158 . Interestingly, HPV proteins can also modulate ROS by regulating GSH and SOD levels 159 . In fact, a relationship between GSH levels in cervical cancer cells and resistance to doxorubicin treatment, an anticancer drug that induces DNA damage and ROS production, was observed 160 .…”
Section: Therapeutic Approachesmentioning
confidence: 99%